If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + 5w + -5t + -6w = 0 Reorder the terms: 8t + -5t + 5w + -6w = 0 Combine like terms: 8t + -5t = 3t 3t + 5w + -6w = 0 Combine like terms: 5w + -6w = -1w 3t + -1w = 0 Solving 3t + -1w = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 'w' to each side of the equation. 3t + -1w + w = 0 + w Combine like terms: -1w + w = 0 3t + 0 = 0 + w 3t = 0 + w Remove the zero: 3t = w Divide each side by '3'. t = 0.3333333333w Simplifying t = 0.3333333333w
| 12x=32-5x^2 | | k^2+28k=0 | | 9h-6h=15 | | -4x+5y=-5 | | -4x+5y=-5t | | 12x=32-5x | | X-7/4-4=x-5/3 | | 166=81-w | | X/3-4=31 | | 7/75=9/x | | 4x/8=3/9 | | 5y-3y+7y=156 | | -27=.3-3s | | 3v-5=v+7 | | 25b-16=3(6b-5) | | 8u=4v-32 | | -3x+5+6x=-10 | | x+62+x+62+70=180 | | 9v^-2/3=16 | | 4(x-5)=-5 | | 3n+5+5n-6= | | X-5/6-1=x-8/7 | | -4x+4y=-28 | | (12/7)=6y | | 11x-5+8x+90=180 | | 5(4-16)=20 | | 4x+5y=-76 | | 63x+9=-36 | | (6/7)*v=42 | | 105=23x+1+11x+2 | | 20x^4-20x^2+3=0 | | 5u+5=-10 |